2009
DOI: 10.1073/pnas.0903460106
|View full text |Cite
|
Sign up to set email alerts
|

A model for DNA polymerase switching involving a single cleft and the rim of the sliding clamp

Abstract: The actions of Escherichia coli DNA Polymerase IV (Pol IV) in mutagenesis are managed by its interaction with the ␤ sliding clamp. In the structure reported by Bunting et al. [EMBO J (2003) 22:5883-5892], the C-tail of Pol IV contacts a hydrophobic cleft on the clamp, while residues V303-P305 reach over the dimer interface to contact the rim of the adjacent clamp protomer. Using mutant forms of these proteins impaired for either the rim or the cleft contacts, we determined that the rim contact was dispensable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
137
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(147 citation statements)
references
References 40 publications
8
137
2
Order By: Relevance
“…Previous efforts to reconstitute this model system for polymerase exchange have involved stalling Pol III on β at a primer terminus by nucleotide omission to synchronize a population of molecules and simulate a lesion-induced block (3,4). These studies were not able to resolve an exchange back to Pol III after Pol IV synthesis.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Previous efforts to reconstitute this model system for polymerase exchange have involved stalling Pol III on β at a primer terminus by nucleotide omission to synchronize a population of molecules and simulate a lesion-induced block (3,4). These studies were not able to resolve an exchange back to Pol III after Pol IV synthesis.…”
mentioning
confidence: 78%
“…S2 A-C, time constant τ decreases from 19.7 to 12.4 s). Biophysical and structural data suggest that only one Pol III binds the clamp dimer (4,18,24,25), arguing that pauses observed during synthesis result from stochastic dissociation of Pol III from the clamp and the diffusionlimited recruitment of a new polymerase from solution (22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, neither DnaE2 nor ImuA′ possesses an identifiable clamp-binding motif (1, 12). The β-clamp modulates the recruitment to the replication machinery of proteins involved in bacterial DNA replication and repair (13), binding replicative and specialist lesion bypass polymerases simultaneously to enable rapid interchange (14,15). The β-clamp-binding motif therefore suggested that ImuB might be crucial for DnaE2 function.…”
mentioning
confidence: 99%